Assessment of internal curing of cellulose microfibers-incorporated cement composites using destructive and nondestructive methods. (17th October 2022) - Gwon, Seongwoo; Ahn, Eunjong; Shin, Myoungsu; Kim, Jin-Yeon; Kim, Gun
Highlights: The use of water-saturated cellulose microfibers (CMFs) facilitates the internal curing and hydration process in cement composites. Development of early-stage material nonlinearity (e.g., microcracks, ITZs, and pores) is mitigated by the addition of CMFs. Hysteresis acoustic nonlinearity parameter ( α ) solely enables capturing the CMFs-induced internal curing effect and mitigation of intrinsic material nonlinearity owing to its high sensitivity. This paper provides quantitative evidence on the potential use of CMFs in concrete mixture for durability enhancement. Abstract: Water-saturated cellulose microfibers (CMFs) incorporated into fresh cement composites can facilitate the internal curing, holding a potential for mitigating intrinsic material defects such as microcracks, interfacial transition zones (ITZs), and pores that raise the material nonlinearity. To elucidate the contribution of water supply from CMFs to internal curing process, this study utilizes the nonlinear impact resonance acoustic spectroscopy (NIRAS) technique. Hysteresis acoustic nonlinearity parameter ( α ) and linear resonance frequency are measured from the NIRAS tests and used to nondestructively quantify the microstructural changes induced by different degrees of internal curing in three different samples (with 0, 0.3, and 1% dosage of CMFs). To get more insight into this phenomenon, other properties including porosity, internal relative humidity (IRH), autogenous shrinkage, compressive strength, and ultrasonic wave velocity are also measured. Evidenced by all measured data, our results confirm that α shows a high sensitivity to the extent of microstructural change in cellulose microfibers-incorporated cement composites, which solely enables capturing time-dependent microstructural changes and thus the discrimination between internal curing effect and development of intrinsic material defects (or material nonlinearity). We believe that this study can lay the foundation for enhancing the durability performance of cement composites via CMFs.